Experimental and Numerical Investigation on an Integrated Thermal Management System for the Li-Ion Battery Module with Phase Change Material. (9th November 2020) - Huang, Qiqiu; Zhong, Zhaoda; Li, Xinxi; Zhang, Guoqing; Wei, Dongyang; Yuan, Weizhong; Zhang, Jiangyun; Zhou, Dequan
Abstract : Lightweight power battery modules with outstanding thermal performance are urgently required given the rapid development of electric vehicles. This study proposes a composite phase change material coupled with forced convection as an integrated thermal management system (ITMS) with the aim to control the temperature's rising tendency and maintain the temperature distribution uniformly within an appropriate range among the battery modules. The thermal behavior effects of airflow rates on the thermal management system were investigated in detail by combining experiments and numerical simulations. Comparisons were conducted between an air cooling system with an optimum flow rate and the ITMS. Experimental results revealed that the cooling effect of the ITMS was better than that of the forced cooling system at a 3 m/s airflow rate. The maximum temperature in the designed battery module was limited to 63.2°C. The maximum temperature difference was limited to 4.8°C at a 4 C discharge rate. This research indicates that the ITMS is an effective and optimized approach to control and balance the temperature among battery modules, thereby providing engineers with design optimization strategies for similar systems.